基于数据挖掘的糖尿病护理研究热点及 前沿趋势分析. - 谭茜; 程金莲; 韩世范; 褚银平; 张月明; 陈琼 (Chinese Nursing Research, 2019)
Objective：To understand the development status of diabetes care，the cooperation ability between authors and institutions， the hot spots in the field of diabetes care and the future research trends in China，so as to provide a reference for Chinese scholars to conduct related researches. Methods：Taking CNKI as the data source，CiteSpace visualization software was used to analyze literatures related to diabetes care from 2000 to 2017. Results：There was no close cooperation between the authors and the institutions in included literatures. The author having the most published articles was DAI Limin，with a total of 11 articles. In terms of the number of published articles，Jilin provincal cancer hospital ranked top one with 68 articles. The research hot spots has focused on hemodialysis nursing of diabetic nephropathy，perioperative nursing for diabetic patients undergoing surgery，diabetic foot nursing and diabetes health education. The research trends of diabetes care has mainly consisted of elderly diabetes，community nursing intervention，clinical nursing pathway， TCM nursing，evidence ⁃ based nursing，compliance，blood glucose control and quality of life. Conclusion：The diabetes care ⁃ related researches have been more and more，and the research scopes have been wider and wider. However，the cooperation ability between authors and institutions has still been insufficient，which needs to be strengthened in the future.